Mechanism of rockburst induced by roadway repair under intense mining: a case study - Ma, Zhenkai; Zhao, Xidong; Li, Sheng (Frontiers in Earth Science, 2024)
Rockbursts involve a sudden failure of the coal and rock mass without any apparent macroscopic precursors, threatening the production safety of coal mines. Achieving precise prediction of potential seismic body of rockbursts and determining their inducing factors are essential for effective prevention and control of rockbursts.By investigating the "1.17" major roof accident in the Danshuigou mine, the distribution characteristics of potential high-energy seismic body in the accident roadway during multi-layer mining were studied, relationship between these characteristics and the surrounding rock damage was established, and mechanism of the high-energy seismic body-induced rockbursts in the roadway was elucidated. It was found that the repair of the roadway floor was a key factor inducing the rockburst occurrence, with multi-layer mining generating potential high-energy seismic body reaching energy densities up to 10 6 J/m 3 , resulting in roadway collapse and severe damage. Greater energy in these seismic body correlates with higher degrees of roadway impact damage. Moreover, higher energy accumulation in surrounding rock during roadway repairs leads to greater energy release. The triggering effects of roadway floor repair construction result in the instantaneous release of large elastic energy accumulated in ultrahigh-energy coal rock bodies, causing rock mass impact damage during triple mining. This study significantly contributes to understanding rockburst mechanisms and enhances the effectiveness of rockburst prediction and prevention.